Takhrij and Syarah Hadith of Chemistry: Shallots in the Perspective of Science and Hadith of the Prophet SAW - Ramdani, Pachrizal; Wibisono, M. Yusuf (Research Parks Publishing LLC, 2021)
The purpose of research is to discuss the hadith prophet saw. About approaching the mosque after eating Onions. This method of research is qualitative through both the earlary approach and the gift shield with a chemical analysis. The results and discussions of this study are the properties and benefits of Onions. The conclusion of this study is the throne and the prophet saw's throne. Regarding the value of Onions to cure disease is seen from the compounds they contain based on chemical analysis.